Online reading strategies of Thai EFL Students - Parnrod, Urarat (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
Reading is mainly known as an important skill. It is widely acceptable that “the more we read, the more we know. We can also gain several benefits of reading, such as developing our imagination and creativity, improving vocabulary and communication, and helping with building a good self-image and playing well with others. To be survived in the fast-changing world, having skills in online reading could be an alternative for the students to be more successful in reading. However, it was found that most studies have focused on reading strategies. Then having more studies about online reading strategies could contribute to language learning and teaching in terms of training the students to employ reading strategies in an online environment effectively and maintaining the stduents’ confidence in language learning. Therefore, this study aims at investigating online reading strategies employed by 43 undergraduate students majoring in English. The questionnaire, Online Survey of Reading Strategies (OSORS), was adapted to elicit the students’ online reading strategies. The quantitative results showed that problem-solving reading strategies were often used when doing online reading activities (Mean = 3.84, SD = 0.94), followed by global reading strategies (Mean = 3.57, SD = 0.93), and support reading strategies (Mean = 3.45, SD = 1.08). Pedagogical implications are also presented in this study.